PENGARUH TINGKAT PENDIDIKAN PEGAWAI TERHADAP KINERJA PEGAWAI PADA KANTOR POS PEMERIKSA RANTAUPRAPAT - Leily, Novrihan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
The purpose of this study was to determine the effect of education level on employee performance at the post office of the rantauprapat examiner. The researcher draws a hypothesis that the level of education has a positive influence on employee performance at the Rantauprapat Examiner Post Office. In this study, 27 samples were taken from the number of employees at the Rantauprapat Examiner Post Office. The variables in the study included 2 variables, namely Education Level as variable X, and Employee Performance as variable Y. Hypothesis testing used t test and regression coefficient, with a significant level of 5%. Data analysis used statistical data processing software, namely SPSS version 22.00 for windows. The data analysis technique in this research is descriptive statistics, simple linear regression analysis, validity test and reliability test. Based on the results of t-test analysis, the independent variable is the level of education (X) of 6.106 â‰¥ t table of 2.064, this means that H0 is rejected and H1 is accepted, or in other words the level of education has an effect on employee performance. From the results of the determinant coefficient (R2) the value is 0.599. This value of 0.599 indicates that the Employee Performance (Y) can explain the Education Level (X) together at 59.9% and the remaining 40.1% is influenced by other factors outside the independent variable.